Onset of plasticity in zirconium in relation with hydrides precipitation. (1st August 2016) - Szewc, W.; Pizzagalli, L.; Brochard, S.; Clouet, E.
Abstract: Molecular dynamics simulations are performed to investigate the onset of plasticity in zirconium, in conditions associated with the formation of hydrides. These simulations show that plasticity is always initiated by the nucleation and propagation of pyramidal partial dislocations from the surfaces, followed by the formation of basal dislocations in a second step. This result is shown to be weakly dependent on several parameters such as surface orientation and roughness, loading conditions, temperature, and interatomic potential. Our analysis based on generalized stacking fault surfaces suggests that the favored activation of pyramidal slip is related to a surface nucleation effect. Finally, the computed elasticity limits are in agreement with the strains associated with the formation of hydride precipitates. Graphical abstract: